Preparation method of nickel-doped carbon quantum dot nano material for efficient photocatalytic reduction of CO2 into methane
By introducing nickel sulfate into carbon quantum dots, the problems of low carbon dot stability and catalytic efficiency in photocatalysis are solved, and the effect of high-efficiency photocatalytic CO2 reduction to CH4 is achieved, and the photocatalysis is broadened Application prospects in the field.
Patent Information
- Application Number
- CN202411285360.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art uses a single carbon dot as a catalyst in photocatalysis to cause problems such as easy recombination of photogenerated electrons and holes, difficulty in regulating the redox capacity and poor stability, resulting in low CO2 reduction yield, impure products and difficulty in separation.
Ni-doped carbon quantum dots (Ni-CDs) were prepared by one-step hydrothermal method and freeze-drying method. By introducing nickel sulfate into the carbon quantum dots, the electron density distribution and energy gap are changed, the light absorption capacity is expanded, and the photocatalytic performance is improved.
It achieves efficient and highly selective photocatalytic reduction of CO2 to CH4, with a yield of 10 times that of pure carbon quantum dots, and the product is pure and easy to separate, solving the problems of low yield and impure product.
Smart Images

Figure HDA0005042973240000011 
Figure HDA0005042973240000012 
Figure HDA0005042973240000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysis technology, and specifically relates to the preparation of nickel-doped carbon quantum dots and the photocatalytic reduction of CO by the nanomaterial. 2 Application in. Background Art
[0002] CO 2 It is the main component of greenhouse gases, and its emissions have been gradually increasing in recent years. 2 The concentration method is particularly important, so the photocatalytic conversion of CO 2 The research on artificial photosynthesis has attracted wide attention. Photocatalysis uses inexhaustible solar energy as a driving force. Currently, a large number of researchers have used different catalytic materials for CO 2 reduction, in which CO 2 Reduction to high-value-added chemical fuels such as methane, carbon monoxide, and methanol is the most attractive method. Therefore, exploring suitable photocatalysts is crucial for the effective implementation of this catalytic process.
[0003] Carbon dots (CDs) are a new type of luminescent zero-dimensional carbon nanomaterials with the characteristics of high stability, low toxicity, and good biocompatibility. They have attracted much attention due to their unique optoelectronic properties and application potential. Their synthesis methods and applications have always been the focus of scientists. The size of CDs is generally below 10nm, and the structure is usually composed of two parts: an sp2 / sp3 amorphous carbon atom center and an outer shell with rich O / N / S functional groups or polymer chains. According to the differences in the microstructure and quantum confinement of the carbon core, fluorescent CDs can be further divided into graphene quantum dots (GQDs), carbon quantum dots (CQDs), carbon nanodots (CNDs) and carbonized polymers (CPDs).
[0004] If carbon dots are used as photocatalysts alone in photocatalysis, there are problems such as easy recombination of photogenerated electrons and holes, difficulty in regulating redox ability, and poor stability. Element doping is a commonly used method for modifying carbon dots, that is, adding specific elements to carbon dots as needed to effectively reduce the band gap and expand the light absorption capacity of carbon dots. Usually, the light absorption efficiency and catalytic efficiency of carbon dots can be improved by doping with precious metals and rare gases. Compared with non-metal atoms, metal ions have more electrons and unoccupied orbitals and larger atomic radii. Doping CDs with metal ions can cause significant changes in light, electronic and magnetic properties by changing the electron density distribution and energy gap, thereby significantly improving the photocatalytic performance of carbon quantum dots.
[0005] Therefore, the present invention adopts a one-step hydrothermal method and freeze-drying method to prepare a Ni-CDs nanomaterial, and further studies the high efficiency photocatalytic CO 2 Reduction to CH 4 rate. Summary of the invention
[0006] The problem to be solved by the present invention is to provide a method for efficiently and selectively photocatalyzing CO 2 Reduction to CH 4 The preparation method of nanomaterials to overcome CO 2 Problems include low reduction yield, impure products, and difficulty in separation.
[0007] The present invention provides a method for preparing nickel-doped carbon quantum dots and photocatalytically reducing CO 2 CH 4 The application mainly involves: preparation and characterization of Ni-CDs nanomaterials, and photocatalytic CO 2 The performance study of reduction is carried out through the following steps:
[0008] Step 1, preparation of nickel-doped carbon dots: lignin is dissolved in deionized water, stirred and then ultrasonicated to form a homogeneous solution, an appropriate amount of ethylenediamine solution is added, and after stirring evenly, an aqueous hydrogen peroxide solution and nickel sulfate are added dropwise. After cooling to room temperature, the solution is transferred into a reactor for hydrothermal reaction to prepare an aqueous solution of nickel-doped carbon dots;
[0009] Step 2: Purification of nickel-doped carbon dots: centrifuge the carbon dot aqueous solution obtained in step 1 to remove the macromolecular substances that have not reacted completely, collect the supernatant for suction filtration, and collect the filtrate after dialysis;
[0010] Step 3: Drying the nickel-doped carbon dots: Freeze the liquid collected in step 2 and then perform freeze-drying to obtain nickel-doped carbon dots.
[0011] The mass of lignin in step 1 is 1.00 g, which is dissolved in 50 mL of water;
[0012] In step 1, the mass ratio of ethylenediamine sampling to lignin is 1 to 5:1, and 1.25 to 6.25 Ll is taken; preferably 5 mL;
[0013] The mass of nickel sulfate in step 1 is 0.26-1.04 g, preferably 0.53 g;
[0014] In step 1, the reaction temperature is 120-200° C., and the reaction time is 8-12 h, preferably 190° C. for 12 h.
[0015] The centrifugation condition in step 2 is 9000 rpm / min for 10 min;
[0016] In step 2, the filtration is performed using a 0.22 μm water filter membrane;
[0017] In step 2, dialysis was performed using a dialysis bag with a molecular weight cutoff of 3500 Da. The dialysis time was 48 h, and the water was changed every 8 h.
[0018] Step 3: Freeze drying: Use a freeze dryer with a cold trap temperature of -60°C and a vacuum degree of 1.0 Pa. The sample must be frozen before using the freeze dryer. After drying, the sample is in a cotton-like state and needs to be ground.
[0019] Step 4: Photocatalytic reduction of CO by nickel-doped carbon quantum dot nanomaterials 2 The invention is characterized in that the specific steps are as follows: dissolving nickel-doped carbon dots in an aqueous solution, placing the nickel-doped carbon dots in an adapted reactor, and using CO 2 The gas cylinder is ventilated continuously to ensure CO 2 The reactor is filled. Samples are taken at given time intervals under specific lighting conditions. Products and product concentrations are determined using high performance gas chromatography.
[0020] In step 4, 10 mg of nickel-doped carbon dots were taken and dissolved in 50 mL of deionized water. 2 The reaction time was 30 minutes. The illumination condition was visible light, provided by a xenon lamp (300W, filter: λ>420nm). Condensed water was passed during the reaction, and the room temperature was always maintained. 1 mL of gas was sampled every 1 hour for detection.
[0021] The present invention characterizes the nickel-doped carbon quantum dot nanomaterial and tests its photocatalytic performance by using instruments such as X-ray powder diffraction, transmission electron microscopy, Fourier transform infrared spectrometer and high performance gas chromatograph.
[0022] Advantages and effects of the present invention
[0023] The present invention uses cheap and readily available lignin as a precursor material to hydrothermally synthesize carbon quantum dots in one step, ethylenediamine as a nitrogen source, and nickel sulfate to provide metal ions to modify the surface groups of carbon quantum dots, thereby realizing one-step hydrothermal synthesis of nickel-doped carbon quantum dots. Not only does it retain the stability, non-toxicity and excellent photoelectric properties of carbon quantum dots, but at the same time, through the doping of metal ions, it effectively reduces the bandgap width, expands the light absorption capacity, and greatly enhances the photocatalytic efficiency.
[0024] Nickel-doped carbon quantum dots achieve efficient and highly selective photocatalysis of CO 2 Reduction to CH 4 , the yield reached 60 μmol in 3 hours, which is about 10 times that of pure carbon quantum dots. No other products were generated, which broadened the scope of photocatalytic reduction of CO 2The practical application of nickel-doped carbon quantum dots can solve the problems of difficult separation of products and impure products. Therefore, nickel-doped carbon quantum dots have broad application prospects in the field of photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the X-ray powder diffraction pattern of carbon quantum dots and nickel-doped carbon quantum dot nanomaterials.
[0026] Figure 2 This is a transmission electron microscope image of nickel-doped carbon quantum dot nanomaterials.
[0027] Figure 3 This is the fluorescence spectrum of nickel-doped carbon quantum dot nanomaterials.
[0028] Figure 4 This is the infrared spectrum of nickel-doped carbon quantum dot nanomaterials.
[0029] Figure 5 Photocatalytic CO catalysis of nickel-doped carbon quantum dot nanomaterials synthesized at different temperatures 2 Reduction product curve.
[0030] Figure 6 The photocatalytic effect of nickel-doped carbon quantum dots on CO 2 Reduction product curve DETAILED DESCRIPTION
[0031] Example 1
[0032] Step 1: Dissolve 1.00 g of lignin in 50 mL of deionized water, stir for 10 min, and ultrasonicate for 30 min to form a homogeneous solution. Add 5 mL of ethylenediamine solution, mix well, and then add hydrogen peroxide solution dropwise.
[0033] Step 2: After the solution is cooled to room temperature, it is transferred into a reaction kettle and reacted in an oven at 190° C. for 12 h to obtain a carbon dot aqueous solution;
[0034] Step 3: Centrifuge the aqueous solution to obtain the supernatant, filter it under a 0.22 μm water filter membrane, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500 Da. Change the water every 8 hours and collect it after 48 hours.
[0035] Step 4: Freeze the aqueous solution and transfer it into a freeze dryer. Set the cold trap temperature to -60°C and the vacuum degree to 1.0 Pa for freeze drying. Grind the obtained flocculent solid into powder in an agate mortar to obtain nickel-doped carbon quantum dot nanomaterials.
[0036] Step 5: Dissolve 10 mg of nickel-doped carbon quantum dot nanomaterials in 50 mL of deionized water and continuously introduce CO into a closed reactor. 2 Gas for 30 minutes to ensure CO2 Fill the reactor. Under the irradiation of a xenon lamp (300W, filter: λ>420nm), sample 1mL of gas every 1h for detection. Use a high performance gas chromatograph to determine the product and its concentration.
[0037] Example 2
[0038] Step 1: Dissolve 1.00 g of lignin in 50 mL of deionized water, stir for 10 min, and ultrasonicate for 30 min to form a homogeneous solution. Add 5 mL of ethylenediamine solution, mix well, and then add hydrogen peroxide solution dropwise.
[0039] Step 2, dissolving 0.53 g of hexahydrate and nickel sulfate in the above homogeneous solution, cooling to room temperature, transferring into a reaction kettle, and reacting in an oven at 190° C. for 12 h to obtain a nickel-doped carbon dot aqueous solution;
[0040] Step 3: Centrifuge the aqueous solution to obtain the supernatant, filter it under a 0.22 μm water filter membrane, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500 Da. Change the water every 8 hours and collect it after 48 hours.
[0041] Step 4: Freeze the aqueous solution and transfer it into a freeze dryer. Set the cold trap temperature to -60°C and the vacuum degree to 1.0 Pa for freeze drying. Grind the obtained flocculent solid into powder in an agate mortar to obtain nickel-doped carbon quantum dot nanomaterials.
[0042] Step 5: Dissolve 10 mg of nickel-doped carbon quantum dot nanomaterials in 50 mL of deionized water and continuously introduce CO into a closed reactor. 2 Gas for 30 minutes to ensure CO 2 Fill the reactor. Under the irradiation of a xenon lamp (300W, filter: λ>420nm), sample 1mL of gas every 1h for detection. Use a high performance gas chromatograph to determine the product and its concentration.
[0043] Example 3
[0044] Step 1: Dissolve 1.00 g of lignin in 50 mL of deionized water, stir for 10 min, and ultrasonicate for 30 min to form a homogeneous solution. Add 5 mL of ethylenediamine solution, mix well, and then add hydrogen peroxide solution dropwise.
[0045] Step 2, dissolving 0.26 g of hexahydrate and nickel sulfate in the above homogeneous solution, cooling to room temperature, transferring into a reaction kettle, and reacting in an oven at 190° C. for 12 h to obtain a nickel-doped carbon dot aqueous solution;
[0046] Step 3: Centrifuge the aqueous solution to obtain the supernatant, filter it under a 0.22 μm water filter membrane, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500 Da. Change the water every 8 hours and collect it after 48 hours.
[0047] Step 4: Freeze the aqueous solution and transfer it into a freeze dryer. Set the cold trap temperature to -60°C and the vacuum degree to 1.0 Pa for freeze drying. Grind the obtained flocculent solid into powder in an agate mortar to obtain nickel-doped carbon quantum dot nanomaterials.
[0048] Step 5: Dissolve 10 mg of nickel-doped carbon quantum dot nanomaterials in 50 mL of deionized water and continuously introduce CO into a closed reactor. 2 Gas for 30 minutes to ensure CO 2 Fill the reactor. Under the irradiation of a xenon lamp (300W, filter: λ>420nm), sample 1mL of gas every 1h for detection. Use a high performance gas chromatograph to determine the product and its concentration.
[0049] Example 4
[0050] Step 1: Dissolve 1.00 g of lignin in 50 mL of deionized water, stir for 10 min, and ultrasonicate for 30 min to form a homogeneous solution. Add 5 mL of ethylenediamine solution, mix well, and then add hydrogen peroxide solution dropwise.
[0051] Step 2, dissolving 1.06 g of hexahydrate and nickel sulfate in the above homogeneous solution, cooling to room temperature, transferring into a reaction kettle, and reacting in an oven at 190° C. for 12 h to obtain a nickel-doped carbon dot aqueous solution;
[0052] Step 3: Centrifuge the aqueous solution to obtain the supernatant, filter it under a 0.22 μm water filter membrane, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500 Da. Change the water every 8 hours and collect it after 48 hours.
[0053] Step 4: Freeze the aqueous solution and transfer it into a freeze dryer. Set the cold trap temperature to -60°C and the vacuum degree to 1.0 Pa for freeze drying. Grind the obtained flocculent solid into powder in an agate mortar to obtain nickel-doped carbon quantum dot nanomaterials.
[0054] Step 5: Dissolve 10 mg of nickel-doped carbon quantum dot nanomaterials in 50 mL of deionized water and continuously introduce CO into a closed reactor. 2 Gas for 30 minutes to ensure CO 2 Fill the reactor. Under the irradiation of a xenon lamp (300W, filter: λ>420nm), sample 1mL of gas every 1h for detection. Use a high performance gas chromatograph to determine the product and its concentration.
[0055] The following test was used to verify the effect of the invention
[0056] 1. Characterization of nickel-doped carbon quantum dot nanomaterials
[0057] The crystalline structures of metal-free carbon quantum dots and nickel-doped carbon quantum dots nanomaterials were characterized by X-ray powder diffraction (XRD). Figure 1 The XRD spectra of metal-free carbon quantum dot nanomaterials and nickel-doped carbon quantum dot nanomaterials are shown in the figure. As shown in the figure, the diffraction peaks of Ni-CDs nanomaterials appear at 25.1° and 41.9°, which are characteristic diffraction peaks of graphite, corresponding to the (002) and (100) crystal planes of graphite, respectively, indicating that CDs and Ni-CDs have a high degree of graphitization. The diffraction peaks of Ni-CDs are slightly offset relative to those of CDs, indicating that the incorporation of metal ions has a slight effect on the crystallization of nanomaterials. There are no extra impurity peaks in the XRD spectrum, indicating that Ni-CDs nanomaterials have excellent crystallinity and purity.
[0058] The morphology of the prepared Ni-CDs nanomaterials was observed by transmission electron microscopy. Figure 2 As shown, the prepared Ni-CDs are regular spherical-like in shape, with a size distribution of 2.5 to 3 nm and a lattice fringe of 0.21 nm, corresponding to the (100) interface of graphitic carbon, indicating that the material is indeed carbon quantum dots.
[0059] The separation and transfer of photogenerated carriers in carbon quantum dot nanomaterials with different nickel doping amounts were compared by fluorescence spectroscopy (PL). Figure 3 As shown in the figure, the PL intensity of Ni-CDs1.0 is significantly lower than that of CDs, Ni-CDs0.5, and Ni-CDs2.0. This fluorescence quenching phenomenon indicates that the prepared Ni-CDs nanomaterials effectively improve the separation efficiency of photogenerated electrons and holes.
[0060] The synthesized nanomaterials were characterized by Fourier transform infrared spectroscopy (FT-IR). Figure 4 shown.
[0061] 2. Photocatalytic reduction of CO 2 Performance Study
[0062] Practical high performance gas chromatography to measure the catalytic reduction of CO by Ni-CDs under 420 nm light irradiation 2 Performance. Figure 5 , 6 As shown, the catalytic products are analyzed and their yields are calculated by detecting the gas and liquid components in the reactor. Figure 5 As shown in the figure, different synthesis temperatures have an impact on the catalytic effect. Through analysis and calculation, the optimal synthesis conditions are 190℃, 12h, CH 4 The yield is 20 μmol / g·h. Figure 6 As shown in Figure 2, the amount of metal doping also affects the catalytic effect. The best nanomaterial is Ni-CDs1.0, CH 4The optimal yield was 20 μmol / g·h. 2 The product is CH 4 The yield was 2 μmol / g·h. Under the same conditions, the optimal yield of Ni-CDs was 20 μmol / g·h, which was 10 times that of CDs.
[0063] In summary, the present invention discloses a highly efficient photocatalytic CO 2 Preparation method of nickel-doped carbon quantum dot nanomaterials for methane and its high selective catalysis of CO 2 CH 4 The Ni-CDs nanomaterials with uniform size and good performance were prepared by a simple one-step hydrothermal method. This not only provides ideas for designing excellent photocatalysts, but also broadens the scope of photocatalytic reduction of CO 2 The practical application of nitrogen-nickel co-doped carbon quantum dots can solve the problems of difficult separation of products and impure products. Therefore, nitrogen-nickel co-doped carbon quantum dots have broad application prospects in the field of photocatalysis.
Claims
1. Preparation of nickel-doped carbon quantum dot nanomaterials for efficient photocatalytic reduction of CO2 to methane, characterized in that: The method proceeds as follows: Step 1, preparation of nickel-doped carbon dots: lignin is dissolved in deionized water, stirred and then ultrasonicated to form a homogeneous solution, an appropriate amount of ethylenediamine solution is added, and after stirring evenly, an aqueous hydrogen peroxide solution and nickel sulfate are added dropwise. After cooling to room temperature, the solution is transferred into a reactor for hydrothermal reaction to prepare an aqueous solution of nickel-doped carbon dots; Step 2: Purification of nickel-doped carbon dots: centrifuge the carbon dot aqueous solution obtained in step 1 to remove the macromolecular substances that have not reacted completely, collect the supernatant for suction filtration, and collect the filtrate after dialysis; Step 3: Drying the nickel-doped carbon dots: Freeze the liquid collected in step 2 and then perform freeze-drying to obtain nickel-doped carbon dots.
2. The method for preparing a nickel-doped carbon quantum dot nanomaterial for efficient photocatalytic reduction of CO2 to methane according to claim 1, characterized in that: The mass of lignin in step 1 is 1.00 g; In step 1, the ethylenediamine solution is 1.25-5 mL; The mass of nickel sulfate in step 1 is 0.26-1.04 g; In step 1, the reaction temperature is 120-200° C. and the reaction time is 8-12 h.
3. The method for preparing a nickel-doped carbon quantum dot nanomaterial for efficient photocatalytic reduction of CO2 to methane according to claim 1, characterized in that: The centrifugation condition in step 2 is 9000 rpm / min for 10 min; In step 2, the filtration is performed using a 0.22 μm water filter membrane; In step 2, dialysis was performed using a dialysis bag with a molecular weight cutoff of 3500 Da. The dialysis time was 48 h, and the dialysate was replaced every 8 h.
4. The method for preparing a nickel-doped carbon quantum dot nanomaterial for efficient photocatalytic reduction of CO2 to methane according to claim 1, characterized in that: Step 3: Freeze drying: Use a freeze dryer with a cold trap temperature of -60°C and a vacuum degree of 1.0 Pa.
5. A nickel-doped carbon quantum dot nanomaterial for efficient photocatalytic reduction of CO2 to methane is prepared by the method described in claims 1 to 4.
6. Use of the nickel-doped carbon quantum dot nanomaterial according to claim 5 in photocatalytic reduction of CO2.
7. Application of nickel-doped carbon quantum dot nanomaterials in photocatalytic reduction of CO2, characterized in that The specific steps are as follows: dissolve nickel-doped carbon dots in aqueous solution, place in an adaptation reactor, use a CO2 cylinder for continuous ventilation to ensure that CO2 fills the reactor; take samples at given time intervals under specific lighting conditions; use a high-performance gas chromatograph to determine the product and product concentration.
8. The method for using nickel-doped carbon quantum dot nanomaterials in photocatalytic reduction of CO2 according to claim 7, characterized in that: The nickel-doped carbon dots were taken in an amount of 10 mg and dissolved in 50 mL of deionized water; CO2 was introduced for 30 min; the illumination condition was visible light, provided by a xenon lamp (300 W, filter: λ>420 nm); condensed water was introduced during the reaction and room temperature was always maintained. 1 mL of gas was sampled every 1 hour for testing.
